UJI METODE CERAMAH DAN TEORI BELAJAR KONTRUKTIVISME UNTUK CARA BELAJAR SISWA MENENGAH PERTAMA NEGERI 2 ARJASA - Dary Farhan Hafizh (Program Studi Pendidikan IPA FKIP Universitas Jember, 2019)
Abstract This study descriptively aims to determine the tendency of learning achievement, using constructivism learning models compared to lecture learning models. Data retrieval is done by observing, giving questionnaires and interviews with the subjects of students from schools of junior high school 2 Arjasa. Descriptive research results show that learning using the lecture learning method provides more understanding to students when compared to the constructivism learning model. Keyword: study; Observation; learning